2020
DOI: 10.1186/s13054-020-02977-5
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota-driven interleukin-17 production provides immune protection against invasive candidiasis

Abstract: Background: The intestinal microbiota plays a crucial role in human health, which could affect host immunity and the susceptibility to infectious diseases. However, the role of intestinal microbiota in the immunopathology of invasive candidiasis remains unknown. Methods: In this work, an antibiotic cocktail was used to eliminate the intestinal microbiota of conventionalhoused (CNV) C57/BL6 mice, and then both antibiotic-treated (ABX) mice and CNV mice were intravenously infected with Candida albicans to invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 78 publications
0
6
0
Order By: Relevance
“…Previous studies have consistently indicated that the administration of levofloxacin can disturb the equilibrium of the intestinal microbiota, thereby inducing antibiotic-associated inflammation within the gastrointestinal tract [55]. Moreover, previous research conducted by our team and other scholars has provided evidence that the depletion of the intestinal microbiota resulting from the administration of antimicrobial drugs substantially elevates the likelihood of bacterial infectious diseases [53,54,[72][73][74]. This correlation is closely linked to the reduction of immunoregulatory metabolites derived from the intestinal microbiota.…”
Section: Discussionmentioning
confidence: 64%
“…Previous studies have consistently indicated that the administration of levofloxacin can disturb the equilibrium of the intestinal microbiota, thereby inducing antibiotic-associated inflammation within the gastrointestinal tract [55]. Moreover, previous research conducted by our team and other scholars has provided evidence that the depletion of the intestinal microbiota resulting from the administration of antimicrobial drugs substantially elevates the likelihood of bacterial infectious diseases [53,54,[72][73][74]. This correlation is closely linked to the reduction of immunoregulatory metabolites derived from the intestinal microbiota.…”
Section: Discussionmentioning
confidence: 64%
“…Many of the microbiota-immune connections noted above were discovered, in part, through the demonstration that these mechanisms of systemic host defense fail when the microbiota is disrupted by antibiotics or absent in GF mice [16][17][18][19][20][21][22][23][24] . Intestinal dysbiosis in both animals and humans has been linked to increased susceptibility to bacterial, viral, and fungal pathogens 20,21,[114][115][116][117] . However, failure of microbiota-dependent host defense mechanisms is not the only consequence of intestinal dysbiosis during infection, as it is now appreciated that dysbiosis can also actively induce pathological systemic inflammation and immune-mediated organ damage in response to infection (ie.…”
Section: Intestinal Dysbiosis and Pathological Systemic Host Response...mentioning
confidence: 99%
“…A systemic candidiasis mouse model was established according to previous studies [20,21], in which the kidney was the primary target organ, and mice developed renal failure and sepsis, and this recapitulated the progressive sepsis seen in humans during severe clinical cases. Firstly, we found that PGRN levels in the kidney, lung, liver, spleen, brain and blood were substantially increased at day 1 and lasted to day 9 after invasive C. albicans infection (Fig 1A).…”
Section: Pgrn Expression Was Up-regulated After C Albicans Infectionmentioning
confidence: 99%
“…immune reactions were an important cause of tissue damage and death in the murine Candida infection model [19][20][21][22]. Despite that PGRN KO mice had similar fungal burden in the kidney, which is the primary infected organ in the systemic candidiasis mouse model, at the early times of C. albicans infection (days 1, 4, and 7), the production of proinflammatory cytokine IL-6, a major cause of sepsis [37,38], in PGRN-deficient mice was significantly lower than that in WT animals.…”
Section: Plos Pathogensmentioning
confidence: 99%
See 1 more Smart Citation